Analysis of the efficiency of application heat-used cooling systems of gas turbine drive air cycle - Volianska, Larysa; Tymoshchuk, Olena; Pikul, Maryna (Science-based technologies, 2020)
It was found that with an increase in temperature at the inlet of the compressor of a gas turbine engine, the efficiency of the installation decreases. The article presents a study of the influence of climatic conditions on the efficiency of the AI-336-1 / 2-10 gas turbine drive intended for the drive of gas pumping units and other industrial installations with a capacity of 10 MW. A method for increasing the efficiency of the installation based on air cooling at the compressor inlet is proposed. Comparison of various existing methods of air cooling at the compressor inlet is carried out. This air preconditioning avoids power loss during hot periods. It is shown that for the best air cooling and, as a consequence, maximizing the performance of a gas turbine unit, it is preferable to use refrigeration units. It seems expedient to cool the air with the help of refrigerating machines that utilize the heat of the exhaust gases. GTU of any circuit design has a high energy potential, what can be used for the production of cold using thermal refrigeration machines: absorption or steam jet. To cool the air at the inlet to the compressor of the AI-336-1 / 2-10 gas turbine drive, the possibility of using a heat-using ejector refrigeration machine was analyzed, which has such advantages as simplicity, small volume and the absence of movable wear parts and the possibility of using water vapor as a refrigerant. In order to determine the magnitude of the decrease in air temperature at the compressor inlet and, accordingly, the increase in the engine efficiency, calculations were performed. The analysis of the efficiency of the gas turbine unit depending on the ambient air temperature and the degree of air cooling in front of the compressor is carried out. The efficiency of the use of a steam jet refrigeration unit for reducing the air temperature at the compressor inlet has been substantiated. It is shown that air cooling at the inlet prevents a decrease in the power of the GTU and ensures the utilization of waste gas heat, leads to an increase in the economic and environmental performance of the installation, and ensures a reduction in fuel consumption. In connection with the foregoing, a detailed study of a technical solution based on the use of a steam-jet refrigeration machine is promising, what reduces the negative effect of high outside air temperatures on the energy and economic efficiency of the gas turbine plant.